Exploration of the moderator effect of cultural diversity on team performance across 45 professional football leagues: An ecological dynamics perspective on cross-cultural research - Darpatova-Hruzewicz, D.; Boski, P.; Kroszka, J. (Psychology of Sport and Exercise, 2022)
Objective To investigate the moderating effect of cultural diversity on team performance in professional football worldwide through the lens of ecological dynamics and cross-cultural psychology.